ANALYSIS OF MARKETING STRATEGIES IN INCREASING SPARE PART SALES VOLUME (Study at Mandiri Motor Workshop Batuphat Timur) - Desti Aninda; Sufi, Sufi; Maisyura, Maisyura; Nursanjaya, Nursanjaya; Lisa Iryani; Nanda Ameliany (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to identify marketing strategies in increasing sales volumes and factors that are inhibiting the implementation of marketing strategy. This research focuses on the marketing strategy of Independent Motor Workshops in improving the volume of sales of spare parts and the factors that hinder the application of marketing policies in Independent Motors Workshops. The theory used from this research is the theory of Kotler and Keller about 4P marketing strategies. This research uses qualitative methods with descriptive approaches. The informants of this research are four informants with purposive sampling and incidental samplings. Data analysis techniques used in research using data reduction, data presentation and conclusion drawings. Based on the results of the research and discussions that have been examined, results of this study show that the 4P marketing strategy used in the implementation of the strategy of the Independent Motor Workshops has greatly increased in terms of application and increase in the volume of sales obtained by the independent motor workshops. The product strategy, price, location and promotion make this enterprise experience a high increase in sales volume.